Exploring the therapeutic potential of isoorientin in the treatment of osteoporosis: a study using network pharmacology and experimental validation - Bo Zhang; Zechao Qu; Hua Hui; Baorong He; Dong Wang; Yong Zhang; Yiwei Zhao; Jingjun Zhang; Liang Yan (BMC, 2024)
Abstract Background Isoorientin (ISO) is a glycosylated flavonoid with antitumor, anti-inflammatory, and antioxidant properties. However, its effects on bone metabolism remain largely unknown. Methods In this study, we aimed to investigate the effects of ISO on receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclast formation in vitro and bone loss in post-ovariectomy (OVX) rats, as well as to elucidate the underlying mechanism. First, network pharmacology analysis indicated that MAPK1 and AKT1 may be potential therapeutic targets of ISO and that ISO has potential regulatory effects on the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) pathways, as well as oxidative stress. ISO was added to RAW264.7 cells stimulated by RANKL, and its effects on osteoclast differentiation were evaluated using tartrate‐resistant acid phosphatase (TRAP) staining, TRAP activity measurement, and F-actin ring analysis. Reactive oxygen species (ROS) production in osteoclasts was detected using a ROS assay kit. The effects of ISO on RANKL-triggered molecular cascade response were further investigated by Western blotting, quantitative real-time polymerase chain reaction, and immunofluorescence staining. In addition, the therapeutic effects of ISO were evaluated in vivo. Results ISO inhibited osteoclastogenesis in a time- and concentration-dependent manner. Mechanistically, ISO downregulated the expression of the main transcription factor for osteoclast differentiation by inhibiting MAPK and PI3K/AKT1 signaling pathways. Moreover, ISO exhibited protective effects in OVX-induced bone loss rats. This was consistent with the results derived from network pharmacology. Conclusion Our findings suggest a potential therapeutic utility of ISO in the management of osteoclast-associated bone diseases, including osteoporosis.